THE INFLUENCE OF MOTIVATION AND WORK FACILITIES ON EMPLOYEE PERFORMANCE: STUDY ON ACADEMIC STAFF OF THE FACULTY OF ADMINISTRATIVE SCIENCE, UNIVERSITAS BRAWIJAYA - Dhea Monica Setia Putri (Erudio Journal of Educational Innovation, 2023)
This study aims to find out how significant and influential it is on employee performance from two variables, namely the motivation variable (x1) and the work facility variable (x2). The dominant-less dominant mix method is being used in this study at Brawijaya University's academic division of the Faculty of Administrative Sciences. An explanatory research approach is being used, using the entire population as a sample of 35 employees using linear regression data analysis techniques duplicates and interviews. From the results of the analysis, it can be concluded that motivation and work facilities simultaneously have a significant influence on employee performance. This is evident from the F test where the data can be seen that the F value is 7.968 > 3.28 (F table) and with a significant F of 0.002 where the significance is smaller or less than 0.05, thus it is found that motivation (x1) and facilities (x2) have an influence on performance (y). Of course, this was also justified by the related party in the interview who said that motivation and work facilities are very important, especially in supporting activities in the academic section. Without motivation at work, of course, employees will be reluctant to do work because of the rolling of the assignment letter given, whereas without facilities that support data input activities, etc. in academic activities, it will be very difficult to work on and will take a long time.